Pengaruh kompetensi sumber daya manusia, pengendalian internal, dan moralitas individu terhadap pencegahan fraud dana desa - Kusumaningrum, Ratna; Wulandari, Ika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Efforts to prevent fraud in the management of village funds are very important for village governments to maintain the sustainability of development and community welfare at the local level. For this reason, the village government can make efforts to prevent fraud that occurs within the village government. This study aims to recognize and test separately the impact of human resource competence, internal control, and individual morality on preventing village fund fraud. Sampling was done using the purposive sampling technique using several criteria, so 34 respondents were taken who met the criteria, including the village head, village secretary, and head of affairs. Hypotheses testing was carried out using multiple linear regression techniques. This study shows that human resource competence and individual morality have no significant effect on preventing village fund fraud. While internal control affects the prevention of village fund fraud, This study provides an understanding of internal control in an effort to increase the prevention of village fund fraud. This research emphasizes that solid internal control has a significant impact on maintaining the security and integrity of village finances.